2000
DOI: 10.1007/s11661-998-0332-6
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic details of precipitates in Fe-22Cr-21Ni-6Mo-(N) superaustenitic stainless steels aged at 900 °C

Abstract: Crystallographic features of second phases and the effect of nitrogen addition on the microstructural evolution in superaustenitic Fe-22Cr-21Ni-6Mo-(N) (all in wt pct) stainless steels during isothermal aging at 900 ЊC were investigated using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Both alloys with and without nitrogen contained sigma phase and M 23 C 6 carbides in the solution treated condition. While four phases (sigma, M 23 C 6 , M 6 C, and chi) of intermetallics and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
78
3
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 35 publications
5
78
3
3
Order By: Relevance
“…It is well known that formation of second phases can cause a decrease in the mechanical properties and corrosion resistance of highly alloyed steels ( Ref 1,2,4,5). For this reason, ASTM A923 Methods A, B, and C have been developed as a means of detecting the presence of intermetallics that may be detrimental to the mechanical properties and corrosion performance of cast duplex alloys .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that formation of second phases can cause a decrease in the mechanical properties and corrosion resistance of highly alloyed steels ( Ref 1,2,4,5). For this reason, ASTM A923 Methods A, B, and C have been developed as a means of detecting the presence of intermetallics that may be detrimental to the mechanical properties and corrosion performance of cast duplex alloys .…”
Section: Introductionmentioning
confidence: 99%
“…Superaustenitic stainless steels are Fe-based systems highly alloyed with Cr, Ni, Mo, and N to produce excellent pitting and crevice corrosion-resistant properties at high temperatures and in seawater (Ref [1][2][3][4][5]. When exposed to elevated temperatures for long periods of time, large amounts of precipitates, including carbides, nitrides, and intermetallic phases, can form in these steels (Ref [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to elevated temperatures for long periods of time, large amounts of precipitates, including carbides, nitrides, and intermetallic phases, can form in these steels (Ref [1][2][3][4][5]. The most commonly observed secondary phases include M 23 C 6 carbide, and intermetallic r, v, and Laves phases (Ref [1][2][3][4][5]. Other less common secondary phases include M 6 C, p, R, and Cr 2 N (Ref [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat treatment at temperatures below 600°C also results in nitride precipitation in the duplex stainless steel of high ferrite content. 9) In almost all the investigations on duplex stainless steels as well as austenitic stainless steels of high nitrogen content, [10][11][12] only hexagonal type nitride Cr 2 N was observed. However, Hertzman reported that cubic CrN might exist in welds of duplex stainless steels.…”
Section: Introductionmentioning
confidence: 99%